2020
DOI: 10.1038/s41419-020-03152-y
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 and MICOS Regulate mitochondrial crista dynamics and formation

Abstract: Mitochondrial cristae are the main site for oxidative phosphorylation, which is critical for cellular energy production. Upon different physiological or pathological stresses, mitochondrial cristae undergo remodeling to reprogram mitochondrial function. However, how mitochondrial cristae are formed, maintained, and remolded is still largely unknown due to the technical challenges of tracking mitochondrial crista dynamics in living cells. Here, using live-cell Hessian structured illumination microscopy combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 41 publications
8
107
0
Order By: Relevance
“…Recent studies using SR techniques showed unexcepted dynamics of cristae [24,66,68,[73][74][75]. Both cristae and CJs constantly changed their position within mitochondria, confirming that they are highly dynamic within seconds [24].…”
Section: Micos Complex Regulates Apparent Cristae Fusion and Fission mentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies using SR techniques showed unexcepted dynamics of cristae [24,66,68,[73][74][75]. Both cristae and CJs constantly changed their position within mitochondria, confirming that they are highly dynamic within seconds [24].…”
Section: Micos Complex Regulates Apparent Cristae Fusion and Fission mentioning
confidence: 91%
“…In recent years, many technical advancements that include live-cell imaging using super-resolution (SR) nanoscopy, focused ion beam-scanning electron microscopy (FIB-SEM), electron tomography (ET), single-particle tracking (SPT) and fluorescence recovery after photobleaching (FRAP) have been used to address the fundamental questions about cristae biogenesis and dynamics [24,25,[66][67][68]. These techniques have allowed unexpected insights into the dynamic nature of cristae and have changed our view of cristae being static entities that only display different shapes under varying circumstances.…”
Section: Understanding Cristae Architecture Using Recent Technologicamentioning
confidence: 99%
“…Recent crystallographic and cryo-EM analyses of OPA1’s yeast homolog Mgm1, provide new insights into how OPA1 remodels the inner membrane to mediate fusion ( Faelber et al, 2019 ; Yan et al, 2020 ). In addition to facilitating inner-membrane fusion, OPA1 promotes dimerization of ATP synthase ( Patten et al, 2014 ) and interacts with the multisubunit Mitochondrial contact site and Cristae Organizing System (MICOS) to help mediate cristae organization in addition to remodeling of the inner membrane ( Hu et al, 2020 ; Stephan et al, 2020 ). Western blot analysis shows five distinct protein isoforms of OPA1: two long (L-OPA1) isoforms that mediate inner-membrane fusion and three short (S-OPA1) fusion-inactive isoforms.…”
Section: Opa1 and Oma1: Stress-sensitive Mitochondrial Fusionmentioning
confidence: 99%
“…However, Opa1 knockout (ko) mouse fibroblasts have also been extremely helpful in understanding the DOA pathogenic mechanism given the clear-cut phenotype due to the complete lack of the protein. Indeed, Opa1 null cells have no fusion activity ( 9 , 46 , 52 , 53 ), decreased the number of mtDNA and nucleoids ( 9 , 53 , 54 ), and caused profound alterations of cristae structure integrity ( 9 , 53 , 55 ). Furthermore, Opa1 ablation and OPA1 overexpression in mouse fibroblasts clarified the interplay between cristae and OPA1 in respiratory chain supercomplexe (RCS) assembly ( 56 ) and identified the ATP synthase as the effector of the OPA1-mediated protection of mitochondrial functions ( 57 ).…”
Section: Opa1 Cell Modelsmentioning
confidence: 99%